SPK Pemilihan Bantuan Bedah Rumah pada Kelurahan Purnama Menggunakan Metode SAW - Putri Yunita (JISKA (Jurnal Informatika Sunan Kalijaga), 2019)
Home renovation assistance is an effort to reduce the burden on the poor. Home renovation is an activity to improve people's houses that are no longer suitable to be occupied. To determine whether or not it is appropriate, residents must meet predetermined criteria. The program that has been running so far is still very complicated in the processing of community data, as well as the selection process for prospective recipients, because it requires precision to determine which families are truly entitled to receive house renovation assistance, because the process is still manual. So we need a decision support system using the saw method that can help in determining who has the right to take precedence in getting home surgery assistance. The purpose in making this application is to help those responsible for making decisions easier, as well as preventing mistakes and fraud and making it easier to determine the values of community data criteria that are truly entitled to receive house renovation assistance. Community data processing for the assessment process can be operated with a computer device through an application system that uses PHP programming and uses a MySQL database Keywords: php, spk, saw method, Home Surgery, system, Javascript